CO2 detection with CNx thin films deposited on porous silicon. (January 2015) - Zouadi, N.; Messaci, S.; Sam, S.; Bradai, D.; Gabouze, N.
Abstract: In recent years, porous silicon (PSi) has attracted a great deal of attention for sensing applications. However, the high reactivity of PSi surfaces causes serious problems of stability. In this work, we developed new thin films that can serve as stabilizer of PSi for CO2 gas sensors development. PSi surface was coated with carbon nitride (CN x ) film which is one of the most important interfering to stabilize the PSi layer. CN x film was deposited by pulsed laser ablation. The effect of CO2 gas on the sensor response was investigated for different polarization voltages. The electrical properties of (Al/CN x /PSi/Si) structure were modified in the presence of the gas. The device shows a high sensitivity against CO2 gas. Furthermore, the current variation of the sensor as a function of time has been investigated. The results show that the Al/CN x /PSi/Si structure becomes stable after the first two weeks.